2000
DOI: 10.1021/bm000284f
|View full text |Cite
|
Sign up to set email alerts
|

Design and Gene Engineering Synthesis of an Extremely Thermostable Protein with Biological Activity

Abstract: A novel strategy for designing and synthesizing extremely thermostable biologically active proteins is proposed. The design concept is based on combining a rigid and extremely hydrophobic peptide unit with a biologically active peptide unit. The cell adhesive peptide sequence, Arg-Gly-Asp (RGD), as a functional peptide unit was incorporated into the elastin-based rigid polyhexapeptide, whose repeating unit is Ala-Pro-Gly-Val-Gly-Val (APGVGV). The designed fusion gene was expressed in E. coli, and the resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 26 publications
2
60
0
Order By: Relevance
“…[2][3][4][5] Artificial ECM proteins have been designed and genetically synthesized in our laboratory. [6][7][8][9][10] Our strategy for the design of artificial ECM proteins relies on the combination of structural peptides and active functional peptides that control cellular functions. One of the ECM proteins previously constructed in our lab, named ERE, is composed of 12 repeats of the elastin-derived APGVGV peptide motif as the stable structural peptide, with the cell adhesive RGD peptide motif as the active functional peptide.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5] Artificial ECM proteins have been designed and genetically synthesized in our laboratory. [6][7][8][9][10] Our strategy for the design of artificial ECM proteins relies on the combination of structural peptides and active functional peptides that control cellular functions. One of the ECM proteins previously constructed in our lab, named ERE, is composed of 12 repeats of the elastin-derived APGVGV peptide motif as the stable structural peptide, with the cell adhesive RGD peptide motif as the active functional peptide.…”
Section: Introductionmentioning
confidence: 99%
“…7 Our genetically designed ECM proteins based on ERE demonstrated applicability as biomaterials. [6][7][8][9][10] However, covalent cross-linking is required to form a hydrogel structure in order to apply our designed ECM proteins to three-dimensional (3-D) culture. 13 The use of cross-linking reagents can result in the loss of the functional peptide's activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sequence is a motif found in elastin which provides a combination of strength and flexibility in the extracellular matrix. We designated the elastin motif as E and the RGD sequence as R. In a previous study we constructed a stable cell adhesive protein which we designated ER4, four repeats of the sequence elastin-RGD (ER) [29]. In the ER4 protein the elastin peptide (E) consisted of 12 repeats of the APGVGV sequence (E12), which has a hydrophobic rigid b-spiral structure, and RGD sequence with cell adhesive function.…”
Section: Introductionmentioning
confidence: 99%
“…One of those, called ER4, consisted of 4 repeats of the fusion construct that conjugated (APGVGV) 12 to the GRGDS sequence. It had been reported that ER4 retained cell adhesive activity due to the incorporated RGDS peptide, 19,20 and therefore ER4 was considered as a positive control for the other artificial fusion ECMs constructed in this study. The EREI2 fusion protein was 2 repeats of (APGVGV) 12 , RGD, (APGVGV) 12 and the IKVAV sequence.…”
Section: Design and Expression Of Fusion Proteinsmentioning
confidence: 99%